Investigations into the coiled tubing partial underbalanced drilling (CT-PUBD) technique for drilling hard formations - Huai-Zhong Shi (KeAi Communications Co., Ltd., 2018)
Abstract To improve the rate of penetration (ROP) in drilling deep and hard formations, this paper proposes a new drilling method called coiled tubing partial underbalanced drilling (CT-PUBD). As a preliminary investigation into the new drilling method, this paper presents predictions of hole cleaning efficiency, drilling speed, cuttings migration and pressure loss in the drilling process with CT-PUBD. Based on numerical simulation and full-scale experimental studies, we conclude that using CT-PUBD, an underbalanced drilling condition can be achieved near the bit while maintaining wellbore safety at the same time. This condition can be achieved using a cuttings discharge device, a rotary packer and a backflow controller. According to the numerical simulations performed in this study, CT-PUBD can achieve high efficiency of hole cleaning. Along the cuttings migration process, the fluid velocities can reach the maximum values in the backflow holes. A full-scale laboratory experimental system was used to test the hydraulic characteristics and obtain the drilling performance of the new technology. The result shows that CT-PUBD significantly improves the ROP compared to the conventional drilling method.